Ecological and Human Health Risks of Nickel Mining: A Systematic Review - Herawati Herawati; Anwar Mallongi; Anwar Daud; Aminuddin Syam; Ridwan Amiruddin; Erniyasih Erniyasih; Shabrina Vashtinia Putri Tryanda (Journal of Public Health and Pharmacy, 2025)
Introduction: The growing global demand for Nickel has sparked major concerns regarding environmental and health impacts, which require a comprehensive understanding. However, there have been gaps in the mapping of study focus and research trends so far, especially in the last ten years. Method: This study aims to address these gaps through a systematic literature review and thematic analysis of 303 articles obtained from Scopus, PubMed, and Springer Open using PoP, Vos Viewer, and Watase Uake. The analysis was conducted by considering trends based on the year of publication, geographical distribution (especially in developing countries such as Indonesia, China, and others), research methodology, and identification of key themes such as heavy metal contamination, land use change, and public health impacts related to mining activities. Results: The study show significant progress in understanding the impacts of nickel mining, but also identify areas that are still underexplored, especially in terms of theoretical development, methodological innovation, and contextual frameworks. The study also found that only 15% of the studies adopted an interdisciplinary approach, indicating the need for more intensive collaboration. These findings highlight the importance of strengthening policy frameworks, especially in areas with intensive mining activities, such as Indonesia. Conclusion: This research proposes a future research agenda to address the emerging challenges and provides important insights for the development of more effective mitigation strategies. The results of this study are expected to contribute to the international policy framework, supporting the design of stronger and region-specific interventions to reduce the environmental and health impacts of nickel mining.